Strong chū‐hai, a Japanese ready‐to‐drink high‐alcohol‐content beverage, and hazardous alcohol use: A nationwide cross‐sectional study. (18th December 2022) - Yoshioka, Takashi; So, Ryuhei; Takayama, Atsushi; Okubo, Ryo; Funada, Satoshi; Takada, Midori; Wakabayashi, Mami; Tabuchi, Takahiro
Abstract: Background: A new ready‐to‐drink premixed high‐alcohol‐content beverage, called strong chū‐hai, was launched in Japan, and more recently, in Taiwan and Australia. We aimed to examine the popularity and association of strong chū‐hai with individual alcohol use, both of which remained unclear. Methods: We conducted a cross‐sectional study using data from the Japan "Society and New Tobacco" Internet Survey conducted from February 1 to 28, 2022, in Japan. We enrolled 27, 993 respondents (aged 15 to 81 years; male 48.5%), including 15, 083 current alcohol users. Using inverse probability weighting of data from the 2016 Comprehensive Survey of Living Conditions on Health and Welfare, we estimated the weighted proportions of strong chū‐hai users among all respondents and constructed multivariable logistic regression models to estimate the weighted odds ratios (OR) and 95% confidence intervals (CI) of strong chū‐hai use for hazardous and harmful alcohol use, defined as a score ≥8 of the Alcohol Use Disorder Identification Test, among current alcohol users. Results: Among all respondents, 56.2% (weighted proportions: past, 35.9%; and current, 20.3%) drank strong chū‐hai . Among drinkers, both past and current strong chū‐hai use, compared to never use, were associated with hazardous and harmful alcohol use (past, OR 1.73, 95% CI 1.42 to 2.12; current, OR 2.19, 95% CI 1.79 to 2.69). Conclusions: Our study found that more than half of the respondents experienced strong chū‐hai consumption, suggesting that it is widely used in Japan. In addition, both past and current strong chū‐hai use were associated with hazardous and harmful alcohol use among current alcohol users. Abstract : A ready‐to‐drink high‐alcohol‐content alcoholic beverage called strong chū‐hai was launched in Japan (2009), Taiwan (2020), and Australia (2021). We examined the proportion and the association of its use with hazardous and harmful alcohol use via a web survey conducted in 2022, Japan. Overall, strong chū‐hai was consumed by more than half of respondents and was associated with hazardous and harmful alcohol use among current drinkers. Our results support the popularity and association of strong chū‐hai with hazardous alcohol use in Japan.